Sklepanje pravnih poslov s povezanimi strankami - Podgorelec, Peter (Podjetje in delo, 2021)
One of the important novelties introduced by Directive 2017/828 is also the arrangement of transactions with related parties through the approval and publication of transaction data as protectionist instruments. With the amendment to the Companies Act (ZGD-1K), a stricter arrangement of transactions with the members of management or supervisory bodies and procurators, and persons associated with them, is provided for, whereby this arrangement - with the exception of the publication of transaction data - is also extended to unlisted public limited companies and middle-sized and large private limited companies. As the body that makes decisions on the approval of a transaction, the supervisory or administrative board is envisaged, which is in line with the principle of adequacy of the body. Furthermore, the amendment to the Companies Act (ZGD-1K) also provides for a special arrangement of the consultancy contract with the members of the supervisory body and modification of the arrangement of the employment contract.
Keywords: approval of transactions; Directive 2017/828; Direktiva 2017/828; implementacija; implementation; objava podatkov o poslu; odobritev posla; posli s povezanimi strankami; publication of transaction data; related party transactions